2014
DOI: 10.1371/journal.pone.0084688
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between the 2012 New CKD-EPI (Chronic Kidney Disease Epidemiology Collaboration) Equations and Other Four Approved Equations

Abstract: ObjectiveThe Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) reported two equations in 2012: one based on cystatin C concentration (CKD-EPI2012cys) and the other using both serum creatinine and cystatin C concentrations (CKD-EPI2012Scr-cys). We compared the adaptability of new formulae with other four equations.MethodsParticipants (n = 788; median age, 54 [range, 19–94] years) were recruited from the First Affiliated Hospital of Nanjing Medical University. The reference glomerular filtration rate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
28
2
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 28 publications
4
28
2
4
Order By: Relevance
“…In the former study, about one twentieth of the population aged 45 years or above were reported to have eGFR < 60 mL/min per 1.73 m 2 (based on a modified Modification of Diet in Renal Disease (MDRD) equation), and one fifth had CKD condition according to the Kidney Disease Outcome Quality Initiative (K/DIGO) criteria . It has been shown from two Chinese population studies, that eGFR estimated by creatinine and cystatin C was always significantly less than that by equation using creatinine only, especially for a measured eGFR of 30 to 89 mL/min per 1.73 m 2 , . The differences in those were less than our results, which may be due to the smaller means of the measured GFRs and the lower proportions in CKD stage 2 & 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In the former study, about one twentieth of the population aged 45 years or above were reported to have eGFR < 60 mL/min per 1.73 m 2 (based on a modified Modification of Diet in Renal Disease (MDRD) equation), and one fifth had CKD condition according to the Kidney Disease Outcome Quality Initiative (K/DIGO) criteria . It has been shown from two Chinese population studies, that eGFR estimated by creatinine and cystatin C was always significantly less than that by equation using creatinine only, especially for a measured eGFR of 30 to 89 mL/min per 1.73 m 2 , . The differences in those were less than our results, which may be due to the smaller means of the measured GFRs and the lower proportions in CKD stage 2 & 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In the original development and validation dataset, the CKD-EPIscr-cys equation performed better than equations based on either marker alone, but the CKD-EPIcys equation did not show obvious advantages over the CKD-EPIscr equation 21. Our previous study indicated that the CKD-EPIscr-cys equation achieved ideal accuracy in nonelderly individuals with normally or mildly injured GFR 29. Validation in the European elderly population suggested that the CKD-EPI equations performed as well in older people as in the younger population.…”
Section: Discussionmentioning
confidence: 95%
“…Yet, only limited data exist outside the development cohort regarding their application in Chinese individuals. In our previous study, CKD‐EPIscr‐cys achieved ideal performance in overall population while Mascr and Mascr‐cys equations appeared more biased and less accurate . Recently, we investigated the application of available equations in the Chinese elderly, of which Fengscr‐cys equation appeared to be optimal in this specific population .…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, CKD-EPIscr-cys achieved ideal performance in overall population while Mascr and Mascr-cys equations appeared more biased and less accurate. 23 Recently, we investigated the application of available equations in the Chinese elderly, of which Fengscr-cys equation appeared to be optimal in this specific population. 24 However, Guo et al suggested that the Fengscr-cys equation showed poorer performance for GFR estimation in Chinese adult CKD patients in comparison with the CKD-EPIscr-cys equation.…”
Section: Discussionmentioning
confidence: 99%